Effects of immersion freezing methods on water holding capacity, ice crystals and water migration in grass carp during frozen storage. (November 2021) - Diao, Yuduan; Cheng, Xinyi; Wang, Lishi; Xia, Wenshui
Highlights: IF reduced thawing loss and maintained the water holding capacity during storage. IF sample had small and uniform distribution of ice crystals during storage. IF sample had a shorter T2 relaxation time during storage. IF effectively maintained the content of unfrozen water during storage. IF was an effective method to reduce water migration of grass carp during storage. Abstract: Recently, immersion freezing (IF) has attracted the attention of many food researchers due to its potential in improving the quality of frozen food. In this study, the effects of air blast freezing (AF), IF and liquid nitrogen freezing (LNF) on the water holding capacity ice crystals, and water migration in grass carp muscles during frozen storage were evaluated. The thawing loss in AF, IF and LNF samples were 13.88 %, 5.49 % and 7.08 %, respectively, and was significantly lower in IF samples than in AF and LNF samples (P < 0.05). Besides, the water holding capacity and pH of all samples gradually decreased during frozen storage. Smaller and more regular intracellular ice crystals were observed in frozen samples during LNF and IF compared with AF. Moreover, IF and LNF had positive effects on the size and distribution of ice crystals. Low field nuclear magnetic resonance (LN-NMR) results showed that IF reduced water migration during frozen storage. In addition, with prolongation of frozen storage time, IF effectively maintained the content of unfrozen water. Therefore, IF can be used as an alternative to the rapid freezing of grass carp with better restriction of water in tissues.